TINJAUAN KRITIS PENGAWASAN POLITIK (POLITICAL OVERSIGHT) DEWAN PERWAKILAN RAKYAT DAERAH TERHADAP FLATFORM KEUANGAN DAERAH (APBD) DI ERA REFORMASI - Maulana, Rio Yusri (Jurusan Ilmu Sosial dan Ilmu Politik Fakultas Hukum Universitas Jambi, 2017)
This article is based on the abberations of the local government implementation. The factors that cause the abberations are the weakness of Parliament Oversight in the discussion and implementations of the Regional Budget Regulation. By using qualitative research methods with the intention of finding out about the factors that cause the abberations and the oversight model that used in the process. Data were collected through library research and documentation, observation and in-depth interviews with a number of informants consisting of local governmen, the Local House of Representatives, Press, and Civil Society that related to the duties and functions of each. These results suggest that the Local House of Representatives has been carrying out Oversight in accordance with its function, but the conduct of such Oversight only in the normative level and a mere formality, without the use of proper oversight models that affect weakness of Parliament Oversight, and make an impacts that cause the abberations in the implementation of the regional budget Regulations. The findings of the research are expected to contribute in the development of scientific study of the concept of governance on legislative oversight toward implementation of Regional Budget Regulation, harmonious and balanced relationship between local government and the Local House of Represetative also be supported by proper model for oversight, and has a rule that can be guiding parliament in carrying out its functions.